Assistance In the Preparation of Teaching Modules Based on Problem Solving Integrated with Character by Utilizing Artificial Intelligence to Junior High School Teachers - Nurhafidhah, Nurhafidhah; Mauliza, Mauliza; Yani, Ahmad Fauzi Syahputra (Unram Journal of Community Service, 2025)
In the Merdeka Curriculum, one of the stages of lesson planning is the preparation of teaching modules. Teaching modules replace the Lesson Plan (RPP) that teachers typically prepare before teaching. Results from interviews with the principal of SMP Negeri 2 Idi Timur revealed two problems: 1) many teachers still do not understand the principles and structure of preparing teaching modules for the Merdeka Curriculum due to limited intensive training they have participated in for module preparation, and 2) teachers' skills in integrating a learning model with Artificial Intelligence (AI) into the teaching module are still lacking. The urgency of this community service lies in the need to optimize teachers' professional competence by providing training on the preparation of teaching modules based on a character-integrated problem-solving model using Artificial Intelligence (AI). The results of the community service activity showed that 40% of participants were very satisfied with the quality of guidance provided in the preparation of character-integrated problem-solving teaching modules using AI, while 45% and 15% were satisfied and somewhat satisfied, respectively. In another question, 60% of participants stated that the guidance helped improve their understanding of teaching modules and the use of AI